Megatrends 2010 : the rise of conscious capitalism - Aburdene, Patricia (Charlottesville, VA : Hampton Roads Pub. Co., 2005)
"The rise of conscious capitalism. Coauthor of best-selling Megatrends 2000 investigates corporate social responsibility; finds that significant numbers of companies are placing social, spiritual, and environmental values ahead of the bottom line; and reports data showing that socially responsible practices actually help boost profits. Identifies eight new trends that will redefine how we work, live, shop, and invest"--Provided by publisher.
The power of spirituality-from personal to organizational -- The dawn of conscious capitalism -- Leading from the middle -- Spirituality in business -- The values-driven consumer -- The wave of conscious solutions -- The "socially responsible" investment boom -- Conclusion: The spiritual transformation of capitalism.
Includes bibliographical references and index.
Keywords: Business -- United States -- Religious aspects; Social responsibility of business -- United States; Business ethics -- United States; Capitalism -- United States -- Religious aspects